The FIFA World Cup Qatar 2022 Sustainability Strategy: Human Rights Governance in the Tripartite Network - O'Rourke, Andrew; Theodoraki, Eleni (Frontiers in Sports and Active Living, 2022)
The Fédération Internationale de Football Association (FIFA) has faced constant accusations of human rights violations associated with World Cup Qatar 2022, with prominent media coverage and international football team demonstrations. This study aims to analyze and discuss the approach taken by the tripartite policy network of actors, namely FIFA, Qatar's Supreme Council (SC), and the Local Organizing Committee (Q22) for the creation of the the FIFA World Cup Qatar 2022 Sustainability Strategy (hereafter WCSS22) published in January 2020. The WCSS22 represents the first time FIFA has clearly articulated its responsibility in connection with impacts that are linked to the construction and operation of World Cup stadia and facilities, in line with the United Nations Guiding Principles on Business and Human Rights (UNGPs). The strategy was also the first to be planned and delivered jointly by FIFA, the SC, and the Q22. Qualitative Content Analysis (QCA) of documents associated with the WCSS22 was performed to answer the following research questions: a) What are the recurrent features of the policy formulation and design process and what role do the UNGPs play? b) How do FIFA and the other policy actors contribute and position themselves in relation to human rights? c) What form did governance (interdependence, interactions, regulated rules, and steering) take in the policymaking process? The study establishes that there are four recurrent features of policy formulation and design: 1) a collective, systematic, and diverse policymaking approach, 2) emphasis on leveraging internal resources and external input, 3) the building foundation of best practice principles, guidelines, strategies, and existing initiatives, and 4) inconsistency on decision-making and accountability measures. FIFA contributes to policymaking primarily through their existing statutes, human rights policy, and commitments to mitigate negative human rights impacts. Furthermore, specified actions, and mechanisms for construction workers' living and working conditions and recruitment processes are articulated by the SC, who take a more prominent role in worker initiatives. Q22, although involved in collective action, and participating in workers welfare, takes a more peripheral role in the policymaking process. In conclusion, it was found that the tripartite policy network of actors represents a participant-based governance approach with cohesive policy formulation, varied resources at their disposal, inconsistencies in accountability measures and with the lead network role dependent on specific actor initiatives and commitments.